The Effect of Classical Guidance Using the Jigsaw Method on Elementary School Students’ Self Control over Mobile Phone Use - Alvin Himawan; Siti Fitriana; Farikha Wahyu Lestari (Indonesian Journal of Guidance and Counseling Studies, 2026)
Background: Uncontrolled mobile phone use among adolescents can lead to behavioral problems and reduced learning quality by disrupting concentration, academic engagement, and social interaction. Therefore, structured guidance interventions are needed to strengthen students’ self-control in managing digital technology use at school. Objective: This study aimed to examine the effect of classical guidance using the jigsaw method on students’ self-control in mobile phone use. Method: A quantitative approach was employed, using a quasi-experimental nonequivalent control group design. The participants were ninth-grade students of SMP Negeri 7 Pemalang. Data were collected using a self-control scale regarding mobile phone use. Statistical analysis was conducted using an independent samples t-test to determine differences between the experimental and control groups. Result: The findings revealed a significant difference in self-control between students who received classical guidance using the jigsaw method and those who did not. The experimental group showed greater improvement in self-control after the intervention than the control group. Conclusion: Classical guidance implemented through the jigsaw method is practical in enhancing students’ self-control in mobile phone use. Contribution: This study enriches the field of guidance and counselling by extending the application of the jigsaw method as an innovative strategy to develop students’ self-control, particularly in addressing challenges related to digital technology use among adolescents.